Insurance and Climate Change Risk Management: Rescaling to Look Beyond the Horizon. (15th April 2018) - Thistlethwaite, Jason; Wood, Michael O.
Abstract: Climate change represents a significant financial risk to the insurance industry, but research has yet to assess whether the industry is managing this risk. Through the application of scale as a vertically nested hierarchy of relationships, this paper seeks to evaluate whether insurers are 'rescaling' risk management practices to accommodate the temporal and spatial uncertainty associated with climate change. This framework is applied to a content analysis of 178 (183) firm responses to the 2012 (2015) U.S. National Association of Insurance Commissioners Climate Risk Disclosure Survey to detect evidence of rescaling through climate change risk management (CCRM). The results reveal that the majority of companies do not integrate climate change into their risk management practices, but reinsurers are rescaling in a greater proportion than primary insurers. This finding confirms that a nested spatial and temporal scale in the insurance industry creates resistance to CCRM. The use of scale contributes to emerging scholarship on organizations and climate change by offering a framework for measuring organizational responses and justifying a research agenda on rescaling strategies as a means of risk management.